Route Optimization In Pharmaceutical Distribution Using Savings Matrix And Nearest Neighbor Heuristics: A Simulation-Based Study - Aldi Musliadin; Dwi Apriadi (Jurnal Riset Ilmu Teknik, 2024)
Drug distribution is one of the important factors in the pharmaceutical supply chain that directly affects operational costs and the speed of customer service. This study aims to optimize the distribution route at XYZ Pharmaceutical Warehouse, which previously used an inefficient delivery pattern, resulting in additional costs and delivery delays. This research implements the Clarke–Wright Saving Matrix and Nearest Neighbor heuristic methods and performs validation using Arena simulation. The analysis results show that the combination of the two methods can reduce the total distribution distance from 121.35 km to 103.90 km, or a reduction of 14.38%. The Nearest Neighbor method produced routes with shorter distances, while the Saving Matrix was superior in maximizing vehicle capacity. Simulations using Arena reinforced the results by showing potential savings in operational time and variable costs, particularly in fuel consumption and driver working hours. These findings confirm that the application of simple heuristic algorithms is still relevant in the context of pharmaceutical distribution, with significant implications for cost efficiency and productivity. Further research is recommended to integrate specific pharmaceutical constraints, such as time windows and cold chain, as well as metaheuristic approaches for more robust solutions.